Analisa Kinerja Bisnis Pada Perusahaan Keluarga (Family Business) Oriental Cap Nyonya Pekalongan - Danang Satrio (Fakultas Ekonomi Universitas Pekalongan, 2017)
Oriental Cap Nyonya Company is one of the beverage industry in bottle packaging which is big enough and able to survive in Pekalongan which has special attraction for writer to make it as research object, because in unpredictable economic condition that is influenced by global crisis, Oriental Cap Nyonya still able to maintain his company to date. The formulation of the problem of this research is how the image of business performance aspects of marketing and human resources in family companies. The purpose of this study is to know the description of business performance aspects of marketing and human resources in family companies. In this study, the indicator of marketing performance is how the company determines the target and the plan for the product and its target market. Human Resource Performance is how companies manage their workers. Keyword : Family Business, Marketing Performance, Human Resource Performance